Flies, genes, and learning. - Waddell, S; Quinn, W (2001)
Flies can learn. For the past 25 years, researchers have isolated mutants, engineered mutants with transgenes, and tested likely suspect mutants from other screens for learning ability. There have been notable surprises-conventional second messenger systems co-opted for intricate associative learning tasks, two entirely separate forms of long-term memory, a cell-adhesion molecule that is necessary for short-term memory. The most recent surprise is the mechanistic kinship revealed between learning and addictive drug response behaviors in flies. The flow of new insight is likely to quicken with the completion of the fly genome and the arrival of more selective methods of gene expression.